Balanced harvesting can emerge from fishing decisions by individual fishers in a small‐scale fishery. Issue 2 (14th July 2016) - Plank, Michael J; Kolding, Jeppe; Law, Richard; Gerritsen, Hans D; Reid, David
Abstract: Catching fish in proportion to their productivity, termed balanced harvesting, has been suggested as a basis for the ecosystem approach to fishing. Balanced harvesting has been criticized as uneconomical and unachievable because of the level of micromanagement it would require. Here, we investigate the consequences of allowing a fixed number of fishers in a small‐scale fishery to choose what size fish to attempt to catch. We examine this from a game‐theoretic perspective and test our predictions using an agent‐based model for fishers' decisions coupled with a size‐spectrum model for the dynamics of a single fish species. We show that small‐scale gillnet fishers, operating without size‐based regulations, would end up catching small and large fish in proportion to their productivity, in other words balanced harvesting. This is significant because it shows that, far from being unachievable, balanced harvesting can emerge without external intervention under some circumstances. Controls are needed to prevent overfishing, but minimum size regulations alone are not sufficient to achieve this, and actually reduce the sustainable yield by confining fishing to a relatively unproductive part of the size‐spectrum. Our findings are particularly relevant for small‐scale fisheries in areas where there is poverty and malnutrition because here provision of biomass for food is more important than the market value of the catch.